SYSTEM CALL: SMART TRASH COLLECTION (STC) DISTRIBUTED PLATFORM FOR THE ON-ROAD COLLECTION OF WASTE FROM OVERPOPULATED CITIES - Ronquillo Lamilla, Cristian; García Pluas, Juan; Varas Chiquito, Michelle; Loor Alcívar, Grace (EASI: Engineering and Applied Sciences in Industry, 2022)
In this research work, the inefficient garbage collection was evidenced, which causes a serious pollution problem. The main objective is to demonstrate that the implementation of a smart architecture makes garbage collection easier. The methodology was descriptive, quantitative, with the use of a sensor simulation, IoT prototype. The expected results indicated that, with the optimized collection of garbage, the reduction of time and costs is generated by the development of smart cities and standards of healthy coexistence. The implementation of SYSTEM CALL: SMART TRASH COLLECTION (STC), advanced architecture, allows waste reduction, detecting overloaded containers through distributed architecture, with RabbitMQ message queue. In conclusion, the use of this scalable architecture is useful for cities which require to reduce environmental impact.
Keywords: Smart waste management; internet of things; smart cities; IoT prototype; data transmission; data Collect; IoT sensors; data simulation